The Interrelation of the Project-Based Approach with Learner-Centered Educational Paradigms and the Competency-Based Model (Journal of Pedagogical Inventions and Practices, 2025)
This article explores the theoretical and practical interrelation between the project-based approach, the learner-centered educational paradigm, and the competency-based model in higher education. It examines how these three frameworks, when integrated, enhance the quality of professional training, foster creativity and independence, and ensure the development of core competencies among students. The paper also presents practical stages for implementing project-based learning in technical disciplines and discusses its outcomes and implications for modern pedagogy